Enhanced precise therapy of ROS-sensitive dual-layer shell nanoparticles loading quercetin on DSS-induced ulcerative colitis mice - Yang Bai; Danling Jiang; Boda Wu; Jiao Peng; Ji Wang; Yuhui Chen; Xi Li (APL Materials)
Ulcerative colitis (UC) is an intestinal condition, involving inflammatory response, apoptosis, and associated processes. As one of the traditional Chinese medicine treatments for UC, quercetin has received attention because it can attenuate inflammation. However, oral administration of quercetin does not perform well in colitis therapy. In this study, reactive oxygen species (ROS)-sensitive nanoparticles (Que@Gel-DA NPs) prepared by self-assembly and polymerization were proposed for the treatment of UC. Quercetin was encapsulated within a shell layer by the self-assembly of gelatin, followed by the polymerization of dopamine on the gelatin surface. Relative to the free form of quercetin, the dual-layer encapsulation enhanced the solubility and bioavailability of quercetin, achieved intragastric protection, and extended the resident time of quercetin in the gastrointestinal tract. Upon reaching the colon lesion, the dopamine shell underwent degradation in response to ROS, and the gelatin shell served to enhance biocompatibility and mitigate quercetin burst release. This resulted in controlled release of quercetin, which enabled precise therapy and exerted antibacterial and anti-inflammatory effects. Furthermore, Que@Gel-DA NPs significantly alleviated the UC symptoms in a dextran sodium sulfate (DSS)-induced UC mouse model. This was evidenced by a significant increase in body weight, a reduction in occult blood in the feces, and a recovery of the crypt structure. The stained results indicated that Que@Gel-DA NPs attenuate inflammation by promoting the polarization of M2 macrophages to reduce apoptosis and modulate immunity. Therefore, Que@Gel-DA NPs, a ROS-sensitive nano-drug delivery system, represent a novel therapeutic approach for the clinical intervention of UC.